2021
DOI: 10.1186/s12889-021-10215-y
|View full text |Cite
|
Sign up to set email alerts
|

Excessive intake of iodine and low prevalence of goiter in school age children five years after implementation of national salt iodization in Shebedino woreda, southern Ethiopia

Abstract: Background Iodine is a trace element required for the synthesis of thyroid hormones. The multiple effects of iodine deficiency on human health are called iodine deficiency disorders (IDDs). IDDs have been common nutritional problems in Ethiopia. In 2012, Ethiopia launched a national salt iodization program to address IDDs. The objective of this study was to assess the effects of this program after 5 years by measuring urinary iodine concentration (UIC) and prevalence of goiter in school age chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 25 publications
1
8
0
1
Order By: Relevance
“…The results showed that there was no significant relationship between palpation of the thyroid gland and the incidence of stunting (p = 1.000). This study is in line with a recent study in Southern Ethiopia which showed a low goiter prevalence and no school children aged 6-12 years had grade 2 goiter [23].…”
Section: Relationship Between Thyroid Gland Palpation With Stunting I...supporting
confidence: 92%
See 1 more Smart Citation
“…The results showed that there was no significant relationship between palpation of the thyroid gland and the incidence of stunting (p = 1.000). This study is in line with a recent study in Southern Ethiopia which showed a low goiter prevalence and no school children aged 6-12 years had grade 2 goiter [23].…”
Section: Relationship Between Thyroid Gland Palpation With Stunting I...supporting
confidence: 92%
“…This study is in line with the recent study of Li et al [22] in 35 low-and middleincome countries who found that no use of iodized salt was significantly associated with the likelihood of stunting. Iodine is an essential trace element for human growth and development and is required for thyroid hormone synthesis [23].…”
Section: Relationship Between the Use Of Iodized Salt And The Inciden...mentioning
confidence: 99%
“…Another study in Anchar district, Eastern Ethiopia, reported a median urinary iodine concentration of 146 μg/L which is comparable with the present study. On the other hand study in Shebedino woreda, southern Ethiopia the higher median urinary concentration, 518 (327 to 704 μg/L) was seen this increment might be because the study was done after the 5 years implementation of the national salt iodization program [16].…”
Section: Discussionmentioning
confidence: 92%
“…We found that Roundup exposure at larvae stages decreased the levels of glucose in the hemolymph of adults. A possible explanation for the decrease in fly hemolymph glucose levels could be that glyphosate leads to a reduction in overall food consumption (Elias et al 2021). Our study is in good agreement with previous studies that have demonstrated that glyphosate decreased the level of glucose in rats Rattus norvegicus (Hasković et al, 2016).…”
Section: Discussionmentioning
confidence: 99%